Synthesis and biological evaluation of 1,2-disubstituted 4-quinolone analogues of Pseudonocardia sp. natural products - Geddis, Stephen M.; Coroama, Teodora; Forrest, Suzanne; Hodgkinson, James T.; Welch, Martin; Spring, David R. (Beilstein Journal of Organic Chemistry, 2018)
A series of analogues of Pseudonocardia sp. natural products were synthesized, which have been reported to possess potent antibacterial activity against Helicobacter pylori and induce growth defects in Escherichia coli and Staphylococcus aureus. Taking inspiration from a methodology used in our total synthesis of natural products, we applied this methodology to access analogues possessing bulky N-substituents, traditionally considered to be challenging scaffolds. Screening of the library provided valuable insights into the structure–activity relationship of the bacterial growth defects, and suggested that selectivity between bacterial species should be attainable. Furthermore, a structurally related series of analogues was observed to inhibit production of the virulence factor pyocyanin in the human pathogen Pseudomonas aeruginosa, which may be a result of their similarity to the Pseudomonas quinolone signal (PQS) quorum sensing autoinducer. This provided new insights regarding the effect of N-substitution in PQS analogues, which has been hitherto underexplored.
Keywords: antibiotics; cross-coupling; heterocycles; quorum-sensing; structure–activity relationships

(untitled) - Heeb, S.; Fletcher, M. P.; Chhabra, S. R.; Diggle, S. P.; Williams, P.; Cámara, M. (FEMS Microbiol. Rev., 2011)

(untitled) - Bisacchi, G. S. (J. Med. Chem., 2015)

(untitled) - Dekker, K. A.; Inagaki, T.; Gootz, T. D.; Huang, L. H.; Kojima, Y.; Kohlbrenner, W. E.; Matsunaga, Y.; McGuirk, P. R.; Nomura, E.; Sakakibara, T.; Sakemi, S.; Suzuki, Y.; et al. (J. Antibiot., 1998)

(untitled) - Rho, T. C.; Bae, E.-A.; Kim, D.-H.; Oh, W. K.; Kim, B. Y.; Ahn, J. S.; Lee, H. S. (Biol. Pharm. Bull., 1999)

(untitled) - Whiteley, M.; Diggle, S. P.; Greenberg, E. P. (Nature, 2017)

(untitled) - Clatworthy, A. E.; Pierson, E.; Hung, D. T. (Nat. Chem. Biol., 2007)

(untitled) - Allen, R. C.; Popat, R.; Diggle, S. P.; Brown, S. P. (Nat. Rev. Microbiol., 2014)

(untitled) - Salvaggio, F.; Hodgkinson, J. T.; Carro, L.; Geddis, S. M.; Galloway, W. R. J. D.; Welch, M.; Spring, D. R. (Eur. J. Org. Chem., 2016)

(untitled) - Cugini, C.; Calfee, M. W.; Farrow, J. M., III; Morales, D. K.; Pesci, E. C.; Hogan, D. A. (Mol. Microbiol., 2007)

(untitled) - Kurosu, M.; Begari, E. (Molecules, 2010)

(untitled) - Geddis, S. M.; Carro, L.; Hodgkinson, J. T.; Spring, D. R. (Eur. J. Org. Chem., 2016)

(untitled) - Bernini, R.; Cacchi, S.; Fabrizi, G.; Sferrazza, A. (Synthesis, 2009)

(untitled) - Ó Muimhneacháin, E.; Reen, F. J.; O’Gara, F.; McGlacken, G. P. (Org. Biomol. Chem., 2018)

(untitled) - Abe, H.; Kawada, M.; Inoue, H.; Ohba, S.-i.; Nomoto, A.; Watanabe, T.; Shibasaki, M. (Org. Lett., 2013)

(untitled) - Mehra, M. K.; Tantak, M. P.; Arun, V.; Kumar, I.; Kumar, D. (Org. Biomol. Chem., 2017)

(untitled) - Lau, G. W.; Hassett, D. J.; Ran, H.; Kong, F. (Trends Mol. Med., 2004)

Basic Research and Clinical Aspects of Pseudomonas Aeruginosa. International Symposium on Pseudomonas Aeruginosa - Sorensen, R. U.; Klinger, J. D. (1987)

(untitled) - Lau, G. W.; Ran, H.; Kong, F.; Hassett, D. J.; Mavrodi, D. (Infect. Immun., 2004)

(untitled) - Smith, W. N.; Beumel, O. F., Jr (Synthesis, 1974)

(untitled) - Wolfe, J. P.; Rennels, R. A.; Buchwald, S. L. (Tetrahedron, 1996)

(untitled) - Janni, M.; Arora, S.; Peruncheralathan, S. (Org. Biomol. Chem., 2016)

(untitled) - Frank, L. H.; DeMoss, R. D. (J. Bacteriol., 1959)

(untitled) - Xiao, G.; Déziel, E.; He, J.; Lépine, F.; Lesic, B.; Castonguay, M.-H.; Milot, S.; Tampakaki, A. P.; Stachel, S. E.; Rahme, L. G. (Mol. Microbiol., 2006)